Glycated Hemoglobin and the Risk of Sternal Wound Infection After Adult Cardiac Surgery: A Systematic Review and Meta-Analysis - Fausto Biancari; Salvatore Giordano (W.B. Saunders, 2022)
Increased glycated hemoglobin (HbA1c) has been shown to increase the riskof mortality, myocardial infarction, and stroke after cardiac surgery, whereasits impact on the development of sternal wound infection (SWI) is less clear.A systematic review and meta-analysis were performed to evaluate theimpact of preoperative HbA1c levels on the occurrence of SWI after adultcardiac surgery. Fourteen studies including 17,609 patients fulfilled theinclusion criteria and were included in this analysis. Diagnostic test meta-analysis of studies evaluating baseline HbA1c cut-off values ranging from6% to 7% DCCT units (4253 mmol/mol IFCC units) showed that the diag-nostic odds ratio for deep SWI was 3.02 (95% confidence interval [CI]2.104.35), while the diagnostic odds ratio for any SWI was 2.81 (95% CI2.023.93). Binary meta-analysis confirmed that baseline HbA1c cut-off val-ues ranging from 6% to 7% increased the risk for deep SWI (pooled inci-dence 2.7% vs 0.8%, risk ratio [RR] 3.01, 95% CI 2.323.90,I20%). Sixstudies included only diabetics and their pooled RR for deep SWI was 2.94(1.595.45,I20%). Nine studies evaluated an HbA1c cut-off value of 7%and their RR for deep SWI was 3.22 (95% CI 2.384.37,I20%). The RR forany SWI was 2.92 (95% CI 2.423.53,I20%). This pooled analysis showedthat the risk of SWI is substantially increased when preoperative HbA1c lev-els are over 67%. Future studies should evaluate whether postponing sur-gery for optimization of the glycemic control can reduce the risk of SWI inpatients with increased levels of HbA1c.Semin Thoracic Surg&&:&&&&© 2019 Elsevier Inc. All rightsreserved.Keywords:Glycated hemoglobin, Glycosylated hemoglobin, HbA1c,Sternal wound infection, Cardiac surgery, Coronary artery bypass grafting